Cross-Linked Electrospun Poly(ethylene oxide) Fiber Mats as Structured Polymer-Gel Electrolytes. (16th July 2015) - Forbey, Scott Joel; Divoux, Gilles M.; Moore, Kate E; Moore, Robert B
Abstract : Poly(ethylene oxide) (PEO) containing pentaerythritol triacrylate (PETA) was electrospun to yield fiber mats that were subsequently crosslinked by exposure to UV irradiation. These mats were then supplemented with lithium perchlorate and swollen with ethylene/dimethyl carbonates to generate a structured polymer-gel electrolyte for Li-polymer battery applications. The fibrous mats were found to be composed of a nonwoven collection of ca. 1μm diameter PEO fibers with up to 85% porosity. Following UV exposure, the mats were rendered insoluble by chemical crosslinking, yielding gel fractions in excess of 80%. Upon incorporation of a liquid lithium ion electrolyte, the swollen mats were shown to maintain the fiberous framework and exhibit conductivities as high as 1.2 × 10 -2 S/cm at room temperature. In contrast, a control mat of electrospun poly(vinylidene fluoride) containing fibers of comparable dimensions and identical electrolyte loading was found to yield a conductivity of only 5 × 10 -3 S/cm.